New Insight into the Electrocatalysis of Ni-Rich Trimetallic NCM-Based Hydroxides for Water Oxidation - Venkatkarthick, Radhakrishnan; Niu, Jingjing; Srikhaow, Assadawoot; Sriprachuabwong, Chakrit; Vasudevan, Subramanyan; Tuantranont, Adisorn; Qin, Jiaqian (ACS applied energy materials, 2021)
Earth-abundant multimetal hydroxides, especially of Ni–Co–Mn-based NCM materials, are very attractive candidates as energy storage materials because of their unique characteristics of synergy with multimetal components, higher electrochemical activity, and lower activation energy compared with a single metal element. The typical hydroxide materials are used as precursors for developing lithium-containing bulk NCM oxide compositions upon calcination with lithium salts at higher temperatures and used as viable cathodes in lithium-ion batteries (LIBs). Nevertheless, the lithium-deficient typical NCM oxide composite (LiNi0.5Co0.2Mn0.3O2 or NCM-523) with a disordered structure was found to have superior electrocatalytic activity than its intact original structure for the water splitting reaction. Herein, we have elaborately investigated the electrocatalytic activity of the typical NCM hydroxide materials without lithium for the two significant compositions, viz., NCM-523 and NCM-811, prepared by a simple co-precipitation method for the oxygen evolution reaction (OER) in an alkaline electrolyte for the first time. Interestingly, the NCM-811 composite exhibits improved catalytic activity with the lowest onset potential (∼1.5 V) and Tafel slope (∼91.7 mV dec–1) for better OER kinetics, whereas the NCM-523 composite exhibits a slightly higher onset potential (∼1.55 V) and Tafel slope (∼175.6 mV dec–1). The ideal composition showed a stable catalytic performance of 25 h continuous water electrolysis. This work can pave ways for the progress of plentiful multi-transition-metal-based hydroxides with virtually tunable compositions for cutting-edge affordable electrocatalytic materials.